WAWASAN AL-QURAN TENTANG KONSERVASI ALAM - Bani Syarif Maula (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
Ecological consciousness in the mid-20th century had a direct effect on the Muslim theological view toward nature. Environmental degradation requires the awareness of all humanity to restore the world to a normal ecological ecosystem based on natural laws, including awareness based on religious texts because Western model conservation is not always in accordance with all cultures and traditions in the world. This paper explains the values contained in the Qur'an associated with ecological awareness because the Qur'an contains the teachings about nature conservation contained in its verses, ranging from problems the creation of the universe until the prohibition of destruction on the face of the earth. The concept of balance (Mizan) and the concept of Islamic Leadership (khalifah) in the Qur'an become the main principle to create social harmony and balance of nature as a foundation to form religious ethics on social life and treatment of nature ethics).